2019
DOI: 10.1128/aac.01628-18
|View full text |Cite
|
Sign up to set email alerts
|

Comparative Genomics of Serial Candida glabrata Isolates and the Rapid Acquisition of Echinocandin Resistance during Therapy

Abstract: The opportunistic pathogen Candida glabrata shows a concerning increase in drug resistance. Here, we present the analysis of two serial bloodstream isolates, obtained 12 days apart. Both isolates show pan-azole resistance and echinocandin resistance was acquired during the sampling interval. Genome sequencing identified nine nonsynonymous SNVs between the strains, including a S663P substitution in FKS2 and previously undescribed SNVs in MDE1 and FPR1, offering insight into how C. glabrata acquires drug resista… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
22
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(24 citation statements)
references
References 21 publications
2
22
0
Order By: Relevance
“…Additionally, it is known that FKS1 and FKS2 mutations can confer resistance to echinocandin drugs in C. glabrata (Katiyar et al, 2012; Arendrup and Perlin, 2014). Consistent with previous studies (Barber et al, 2018), the second isolate of the pair NRZ-2016-057/NRZ-2016-058 presented a non-synonymous mutation in FKS2 (S663P), which correlated with the acquisition of echinocandin resistance. The original comparison of the two echinocandin resistant strains, CMRL2 and CMRL4, with their susceptible paired strains, reported mutations in FKS1 (S629P) and FKS2 (S663P), respectively (Biswas et al, 2017).…”
Section: Resultssupporting
confidence: 90%
See 3 more Smart Citations
“…Additionally, it is known that FKS1 and FKS2 mutations can confer resistance to echinocandin drugs in C. glabrata (Katiyar et al, 2012; Arendrup and Perlin, 2014). Consistent with previous studies (Barber et al, 2018), the second isolate of the pair NRZ-2016-057/NRZ-2016-058 presented a non-synonymous mutation in FKS2 (S663P), which correlated with the acquisition of echinocandin resistance. The original comparison of the two echinocandin resistant strains, CMRL2 and CMRL4, with their susceptible paired strains, reported mutations in FKS1 (S629P) and FKS2 (S663P), respectively (Biswas et al, 2017).…”
Section: Resultssupporting
confidence: 90%
“…In addition, five other pairs of isolates (DSY562/DSY565, NRZ-2016-057/NRZ-2016-058, CMRL1/CMRL2, CMRL3/CMRL4, and CMRL5/CMRL6) included in this study, have been shown to present different resistance profiles to antifungal drugs (Supplementary Table S5). DSY565, CMRL6, NRZ-2016-057, and NRZ-2016-058 were shown to be azole resistant; and CMRL2, CMRL4, and NRZ-2016-058 were shown to be echinocandin resistant (Biswas et al, 2017; Vale-Silva et al, 2017; Barber et al, 2018).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Unlike S. cerevisiae , however, C. glabrata is an obligate human commensal microbe that can become pathogenic and is a leading cause of life-threatening invasive fungal infections in immunocompromised individuals 1315 . C. glabrata rapidly develops resistance to different antifungal drug classes 12,1620 and is characterized by extremely high genome variation among clinical isolates both in terms of single nucleotide polymorphisms and larger structural variants 912,21 . The documented extensive chromosomal variation among C. glabrata clinical isolates resembles the unstable karyotypes and increased gross chromosomal rearrangements observed in S. cerevisiae mutants lacking DNA replication checkpoint functions 22,23 .…”
Section: Introductionmentioning
confidence: 99%